Khảo sát khả năng hấp phụ ion Cu (II) bằng hydrogel trên cơ sở Poly(vinyl alcohol)/ chitosan/carbon - Nguyên, Bùi Thị Thảo; Trự, Nguyễn Nhị; Anh, Hà Thị Trâm; Giao, Nguyễn Thị Quỳnh; Hân, Huỳnh Thị Ngọc; An, Nguyễn Đức (Tạp chí Khoa học Đại học Cần Thơ, 2023)
Abstract – Hydrogels have attracted the attention of domestic and foreign researchers due to their outstanding properties such as simple fabrication and diverse applications in many fields. In this study, hydrogels were synthesized from polyvinyl alcohol (PVA), chitosan (CS), and activated carbon (AC) towards removing copper ions from wastewater. The characteristic properties of hydrogels were investigated by analytical methods, including infrared spectroscopy (FTIR), X-ray diffraction (XRD), water swelling behavior, and Cu (II) ion adsorption capacity. The maximum water swelling capacity of the hydrogel was 497.1% when the active carbon content in the hydrogel sample was 2 wt%. The Langmuir and Freundlich isotherm models were used in the study to evaluate the Cu (II) ion adsorption capacity of the hydrogel and the experimental parameters of the survey process completely matched the model. The PVA/chitosan/active carbon hydrogel achieved a maximum Cu (II) ion adsorption of 212.766 mg/g in neutral medium.